2015
DOI: 10.5603/cj.a2014.0056
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular filling pressure in male patients with type 2 diabetes and normal versus low total testosterone levels

Abstract: Background: Heart failure is a common complication of diabetes characterized by an elevation in left ventricular filling pressures (LVF) that often develops in the absence 94 ± 0.10 vs. 1.19 ± 0.12 (p = 0.01), deceleration time 242 ± 7.4 ms vs. 205 ± 9 ms (p = 0.026) (Cardiol J 2015; 22, 2: 206-211)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The cohort clinical study demonstrated that the prevalence of cardiovascular morbidity and mortality increased in patients suffering from prostate cancer (PCa) who have undergone to androgen deprivation therapy (ADT), suggesting that testosterone deficiency was the risk factor of cardiovascular diseases (Gandaglia et al 2015). Moreover, diastolic dysfunction was found in patients with type 2 diabetes with low testosterone level compared with similar patients with normal testosterone levels (Tinetti et al 2015). Furthermore, patients suffering from congestive heart failure (Jankowska et al 2006) and coronary artery disease (Li et al 2012) have been shown to have lower levels of testosterone compared with healthy men, and the severity of these conditions had a strong correlation with the degree of testosterone deficiency (Li et al 2012, Oskui et al 2013.…”
Section: Metabolic Disturbancementioning
confidence: 99%
“…The cohort clinical study demonstrated that the prevalence of cardiovascular morbidity and mortality increased in patients suffering from prostate cancer (PCa) who have undergone to androgen deprivation therapy (ADT), suggesting that testosterone deficiency was the risk factor of cardiovascular diseases (Gandaglia et al 2015). Moreover, diastolic dysfunction was found in patients with type 2 diabetes with low testosterone level compared with similar patients with normal testosterone levels (Tinetti et al 2015). Furthermore, patients suffering from congestive heart failure (Jankowska et al 2006) and coronary artery disease (Li et al 2012) have been shown to have lower levels of testosterone compared with healthy men, and the severity of these conditions had a strong correlation with the degree of testosterone deficiency (Li et al 2012, Oskui et al 2013.…”
Section: Metabolic Disturbancementioning
confidence: 99%
“…A study in men with acute heart failure reported that low circulating T level was related to worse LV diastolic dysfunction 25 . Similarly, another study in men with asymptomatic type 2 diabetes 26 or with type 2 diabetes without structural heart diseases also found that low T was related to the increased LV filling pressure represented by higher E/e’. On the other hand, some studies have suggested T supplementation after myocardial infarction may worsen the patients’ symptoms 27 29 , and Culic et al postulated that T was beneficial only for relatively normal hearts 30 .…”
Section: Discussionmentioning
confidence: 79%